Antimicrobial Activity of Sorghum Phenolic Extract on Bovine Foodborne and Mastitis-Causing Pathogens - Sydney E. Schnur; Raghavendra G. Amachawadi; Giovanna Baca; Sarah Sexton-Bowser; Davina H. Rhodes; Dmitriy Smolensky; Thomas J. Herald; Ramasamy Perumal; Daniel U. Thomson; Tiruvoor G. Nagaraja (MDPI AG, 2021)
Antimicrobial resistance in bacterial pathogens associated with bovine mastitis and human foodborne illnesses from contaminated food and water have an impact on animal and human health. Phenolic compounds have antimicrobial properties and some specialty sorghum grains are high in phenolic compounds, and the grain extract may have the potential as a natural antimicrobial alternative. The study's objective was to determine antimicrobial effects of sorghum phenolic extract on bacterial pathogens that cause bovine mastitis and human foodborne illnesses. Bacterial pathogens tested included Escherichia coli, Salmonella Typhimurium, Campylobacter jejuni, Campylobacter coli, Pseudomonas aeruginosa, Klebsiella pneumoniae, Klebsiella oxytoca, Staphylococcus aureus, and Enterococcus faecalis. Antibacterial activities of sorghum phenolic extracts were determined by agar-well diffusion assay. Sorghum phenolic extract was added to the wells in concentrations of 0, 100, 200, 500, 1000, or 4000 µg/mL. The control wells did not receive phenolic extract. Plates were incubated for 18-24 h, and the diameter of each zone of inhibition was measured. The results indicated that sorghum phenolic extract had inhibitory effects on Staphylococcus aureus, Enterococcus faecalis, Campylobacter jejuni, and Campylobacter coli.